2021
DOI: 10.3389/fphar.2020.596362
|View full text |Cite
|
Sign up to set email alerts
|

Depression with Comorbid Diabetes: What Evidence Exists for Treatments Using Traditional Chinese Medicine and Natural Products?

Abstract: Comorbidity between diabetes mellitus (DM) and depression, two chronic and devastating diseases spreading worldwide, has been confirmed by a large body of epidemiological and clinical studies. Due to the bidirectional relationship between DM and depression, this comorbidity leads to poorer outcomes in both conditions. Given the adverse effects and limited effectiveness of the existing therapies for depression associated with diabetes, the development of novel therapeutic drugs with more potency and fewer side … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 115 publications
(114 reference statements)
1
13
0
1
Order By: Relevance
“…[ 25 ] Herbal medicine, in particular, is a complex ingredient that acts through various mechanisms and has therapeutic effects on CCD, in which various symptoms are complicatedly intertwined. [ 26 28 ]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 25 ] Herbal medicine, in particular, is a complex ingredient that acts through various mechanisms and has therapeutic effects on CCD, in which various symptoms are complicatedly intertwined. [ 26 28 ]…”
Section: Discussionmentioning
confidence: 99%
“…[25] Herbal medicine, in particular, is a complex ingredient that acts through various mechanisms and has therapeutic effects on CCD, in which various symptoms are complicatedly intertwined. [26][27][28] A previous systematic review [17] suggested that oral herbal medicines for PHN may be effective and safe for pain relief. However, these results should be interpreted with caution owing to methodological issues, the low quality of the included RCTs, or problems with the selection criteria used.…”
Section: Discussionmentioning
confidence: 99%
“…These altered miRNAs (rno-miR-879-5p, rno-miR-7a-5p, rno-miR-499-5p, rno-miR-495, rno-miR-204-5p, rno-miR-199a-3p, rno-miR-151-3p, rno-miR-144-3p, rno-miR-24-3p, rno-miR-25-3p, and rno-miR-21-5p) targeting differentially expressed mRNAs ( Btg2 , Slc39a12 , Calml4 , Foxs1 , Nr1d1 , Ntrk2 , Tnfaip6 , Arc , Ntf3 , GAT-3 , VGAT , Gad1 , and Bdnf ) were attributed to the neurotrophic, MAPK, PI3K-Akt, and cAMP signaling pathways, alanine, aspartate and glutamate metabolism, GABAergic synapse, and circadian rhythm. These signaling pathways were also involved in the anti-depression and anti-anxiety efficacy of current alternative therapy including TCM formula, Chinese herbs, extract, acupuncture, massage, exercise, and in experimental manipulations with fast-acting antidepressant-like (ketamine) activity [ 6 , 71 76 ].…”
Section: Discussionmentioning
confidence: 99%
“…This persistent incapacity for treating depression efficiently results in part from the heterogeneity of the disorder and the insufficient understanding of the functional and molecular mechanisms underlying its onset [ 4 ]. Hence, this is urgent need for immediate and effective treatments for depression with fewer adverse events, and complementary and alternative medicinal therapies, particularly traditional Chinese medicine (TCM), are widely tested for this purpose [ 5 , 6 ]. TCM is a holistic treatment which emphasizes the integration of a variety of biological systems in the human body and the plants represent important raw materials for new compounds that warrant further investigation.…”
Section: Introductionmentioning
confidence: 99%
“…28 In patients with DM and depressive disorders, a wide variety of disturbances may affect the central nervous systems, including the overactivation of the HPA axis, decreased monoamine neurotransmitters, and dysfunctional brain-derived neurotrophic factor. 29 Several mechanisms have been suggested by which BDNF influences depression in T2DM. Since BDNF forms have opposing effects on cell survival, 'yin and yang' model of neurotrophin action has been suggested.…”
Section: Assessment Of Serum Bdnf Levelsmentioning
confidence: 99%